Where Is Ana Mendieta? : Identity, Performativity, and Exile - Blocker, Jane (Book collections on Project MUSE., 1999)
Ana Mendieta, a Cuban-born artist who lived in the exile in the US, was one of the most provocative personalities of the 1970s art world. This text provides a critical analysis of Mendieta's diverse body of work, considering feminism, multiculturalism and postmodernism.